Voice acoustic profi le of males exposed to occupational infrasound and low-frequency noise - Mendes, Ana (2016)
Background: Vibroacoustic disease (VAD) is a systematic pathology characterized by the abnormal growth of extra-cellular matrices in the absence of infl ammatory processes, namely collagen and elastin, both of which are abundant in the basement membrane zone of the vocal folds. VAD can develop due to long-term exposure to infrasound and low-frequency noise (ILFN, <500 Hz). Mendes et al. (2006, 2008 and 2012) revealed that ILFN-exposed males and females presented an increased fundamental frequency (F0), decreased jitter %, and reduced maximum phonation frequency range, when compared with normative data. Temporal measures of maximum phonation time and S/Z ratio were generally reduced. Study Aims: Herein, the same voice acoustic parameters of 48 males, 36 airline pilots and 12 cabin crewmembers (age range 25-60 years) were studied, and the effects and interaction of age and years of ILFN exposure were investigated within those parameters. ILFN-exposure time (i.e. years of professional activity) ranged from 3.5 to 36 years. Materials and Methods: Spoken and sung phonatory tasks were recorded with a DA-P1 Tascam DAT and a C420III PP AKG head-worn microphone, positioned at 3 cm from the mouth. Acoustic analyses were performed using KayPENTAX Computer Speech Lab and Multi-Dimensional Voice Program. Results: Results revealed that even though pilots and cabin crewmembers were exposed to occupational environments with distinct (ILFN-rich) acoustical frequency distributions and sound pressure levels, differences in the vocal acoustic parameters were not evident. Analyzing data from both professional groups (N = 48) revealed that F0 increased signifi cantly with the number of years of professional activity. Conclusion: These results strongly suggest that the number of years of professional activity (i.e. total ILFN exposure time) had a signifi cant effect on F0. Furthermore, they may refl ect the histological changes specifi cally observed on the vocal folds of ILFN-exposed professionals.